EXPERIENCE OF DEVELOPED COUNTRIES IN THE FIELD OF OPTIMIZATION OF PUBLIC PROCUREMENT - Исраилов Баходир (Ecominds Press, 2026)
The article discusses the international experience of optimizing the public procurement system based on the practices of leading foreign countries. Particular attention is paid to the digitalization of procurement procedures, increasing transparency and reducing corruption risks. The analysis of approaches used in the countries of the European Union, the USA, South Korea and Singapore is carried out, and conclusions are formulated on the possibility of adapting these practices in national public procurement systems.
Keywords: Public procurement, optimization, digitalization, transparency, international experience.